(untitled) (Our Nature, 2013)
Drains have been widely used to treat dry land salinity and removing excessive water from wetland area. The main aim of this study is to evaluate the impact on vegetation by deep and open drains. Aerial images of two different time interval were evaluated by using dot grid overlaid method. Deep and open drain had significantly changed the vegetation composition of study area. Proportional coverage of bare ground had increased by 132.9%. Conversely, the proportional coverage of lakes, shrubs and grassland had decreased by 26.1., 21.1 and 3.9%, respectively. The impact was severe in the wetland landscape in comparison to the pasture landscape. DOI: http://dx.doi.org/10.3126/on.v11i1.8244 Our Nature Vol.11(1) 2013: 54-60